Ideology and human rights: the common - Fernández García, Eusebio (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
In our time, we witness a true proliferation of rights. There is no conflict or human problem that doesn’t lead to a debate about the rights we have and whose protection we demand. Such a scenario gives rise to the emergence of multiple challenges for a theory of human rights. These challenges can be both theoretical and practical. This paper points out a peculiar theoretical challenge: the need to clarify and determine very well the scope of any political ideology that contains a theory of human rights. Currently, the theory of the Common has been chosen in order to compare it with the political consequences of two theories that, in some way, have historically preceded it: J.J. Rousseau’s General Will and C. Marx’s proposal of a generic being.
Keywords: the Common; possessive individualism